2019
DOI: 10.1002/adsc.201900225
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I)‐Catalyzed Regioselective Chan‐Lam N2‐Vinylation of 1,2,3‐Triazoles and Tetrazoles

Abstract: Copper‐catalyzed coupling of π‐deficient NH‐azoles with vinylboronic acids or vinyltrifluoroborate salt provides a direct route to N2‐vinyl‐1,2,3‐triazoles and N2‐vinyltetrazoles. The coupling reaction is efficiently catalyzed by (phen)Cu(PPh3)Br with low catalyst loading (5 mol%) under base‐free conditions. The method is applicable for vinylation of unsubstituted, monosubstituted, and disubstituted 1,2,3‐triazoles with various functionalities with high N2‐selectivity.magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…47 This complex could coordinate with the alkyne moiety of 2 to give the copper complex II , which then underwent 5- endo-dig cyclization to form the 3-copper indole intermediate III . The deprotonation of III generated intermediate IV , which was first oxidized by air to give a Cu( iii ) 48,49 intermediate V followed by reductive elimination to furnish the desired product 3 and Cu( i ) species.…”
Section: Resultsmentioning
confidence: 99%
“…47 This complex could coordinate with the alkyne moiety of 2 to give the copper complex II , which then underwent 5- endo-dig cyclization to form the 3-copper indole intermediate III . The deprotonation of III generated intermediate IV , which was first oxidized by air to give a Cu( iii ) 48,49 intermediate V followed by reductive elimination to furnish the desired product 3 and Cu( i ) species.…”
Section: Resultsmentioning
confidence: 99%
“…In 2019, Latyshev and co-workers reported an efficient copper(I)-catalyzed N 2 -vinylation of 1,2,3-triazoles 77 with vinylboronic acids or vinyltrifluoroborate salt 78 (Scheme 27). 39 Different from the classical Chan-Lam coupling, air-…”
Section: Scheme 25 Synthesis Of 2-allenyl-123-triazoles Through Iron-...mentioning
confidence: 99%
“…In 2019, Latyshev and co-workers reported an efficient copper(I)-catalyzed N 2 -vinylation of 1,2,3-triazoles 77 with vinylboronic acids or vinyltrifluoroborate salt 78 (Scheme 27 ). 39 Different from the classical Chan–Lam coupling, air-stable Cu(I) complex (phen)Cu(PPh 3 )Br was used as a new catalyst to enable the reaction with low catalyst loading (5 mol%) under base-free conditions. This method was suitable for the vinylation of un-, mono- and disubstituted 1,2,3-triazoles 77 , especially when the C-4 position was substituted by bromine or fluorine, which resulted in high N 2 selectivity.…”
Section: N 2 -Alkenylationmentioning
confidence: 99%
“…[ 26 ] In 2019, Motornov et al developed regioselective N 2 ‐arylation of 1,2,3‐triazoles/tetrazoles employing vinylboronic acids or vinyltrifluoroborate salt as reaction reagents in the presence of 5 mol% (phen)Cu(PPh 3 )Br as a catalyst. [ 27 ] Recently, Akatyev et al studied the catalytic activity of copper complexes with different ligands in Chan–Lam coupling and demonstrated that the dinuclear positively charged copper complex derived from 4‐ t‐ butyl‐2,5‐bis[(quinolinylimino)methyl]phenolate was excellent catalysts for this reaction. [ 28 ] The related evidence indicated that the reaction mechanism of Chan–Lam coupling catalyzed by the dinuclear copper complex might include the Cu(II)/Cu(II) pair, which were coordinated by an oxygen molecule in the formation of CN bond, different from the previous mechanism involving conversion of the Cu(II) complexes to Cu(I) propose by King et al [ 29 ] and Vantourout et al [ 30 ] In addition, hexadentate NHC–copper hydroxide complex [ 31 ] and tetradentate copper(II)–NHC complex [ 32 ] were also synthesized and applied in the coupling reaction of arylboronic acids with nitrogen‐containing nucleophiles.…”
Section: Introductionmentioning
confidence: 99%